Genetic diversity assessment of sorghum (Sorghum bicolor (L.) Moench) accessions using single nucleotide polymorphism markers. Issue 5 (10th October 2019) - Afolayan, G.; Deshpande, S. P.; Aladele, S. E.; Kolawole, A. O.; Angarawai, I.; Nwosu, D. J.; Michael, C.; Blay, E. T.; Danquah, E. Y.
Abstract: Sorghum ( Sorghum bicolor (L.) Moench) is an important resource to the national economy and it is essential to assess the genetic diversity in existing sorghum germplasm for better conservation, utilization and crop improvement. The aim of this study was to evaluate the level of genetic diversity within and among sorghum germplasms collected from diverse institutes in Nigeria and Mali using Single Nucleotide Polymorphic markers. Genetic diversity among the germplasm was low with an average polymorphism information content value of 0.24. Analysis of Molecular Variation revealed 6% variation among germplasm and 94% within germplasms. Dendrogram revealed three groups of clustering which indicate variations within the germplasms. Private alleles identified in the sorghum accessions from National Center for Genetic Resources and Biotechnology, Ibadan, Nigeria and International Crop Research Institute for the Semi-Arid Tropics, Kano, Nigeria shows their prospect for sorghum improvement and discovery of new agronomic traits. The presence of private alleles and genetic variation within the germplasms indicates that the accessions are valuable resources for future breeding programs.